Firm heterogeneity, labour marketing pooling, and the formation of local labour markets - Konrad O. Stahl; Uwe Walz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
We investigate the simultaneous impact of output and input market imperfections on the characteristics and size of regional economic activity. Firms, producing imperfect Substitutes, face product specific demand shocks which translate into firm-specific shocks. The more different the products are the less correlated the shocks. Then, larger regions provide a better hedge for firms. With heterogeneity on the output side labour demand of firms tends to become also more heterogenous, leading to higher retraining costs for workers in the case of a job loss. Since adjustment costs prove to be higher in larger regions, workers demand higher wages there, imposing thereby higher labour costs on firms. We analyze this trade-off and ask for the resulting firm characteristics in different regions, the interregional wage dispersion, as well as the impact on the regional distribution of economic activity.
Keywords: 330; Regionalökonomik; Produktdifferenzierung; Regionaler Arbeitsmarkt; Arbeitsmarktsegmentation; Räumliche Interaktion; Regionale Lohnstruktur; Theorie